PEMODELAN PROSES ELEKTROLISIS UNTUK PENGOLAHAN AIR YANG MENGANDUNG BESI - Irwan Bagyo Santoso (NIM : 25397021), R.
Abstract : Modeling of electrolysis process has been conducted for water treatment contained ferrous was used artificial raw water with controllable level and type of ferrous. The influence of some parameters in electrolysis process can be predicted by experiment used model of electrolysis process reactor. The experiment used batch model , some parameters that influence process are : current , initial concentration , area of electrode , type of ferrous , and distance of electrode. On the other hand , the experiment used reactor model with continous flow , the parameters that influence the process are : current, area of electrode , flow and type of ferrous . The results of experiment are process equation for batch reactor as follow : Zero orde reaction ( initial process) : Ct=Co-Kl.t where : KI = -2.1027.10<sup<-3- 1.3526.10-1.I-I.8351.10-5.Co-1.4412:10-6.A+ 2.5537.10-4.x+2.0567,10-3.n First orde reaction ( after zero orde ) In Ct = In C\' - (K2.(t-t\')) where : K2 = -1.4347.10-4 -6.9085.10-4.I+ 1.6117 .10-5.lnCo - 8.7714. 10-9. A+3 . 3 927.10-5. n The results of experiment are process equation for continous flow reactor as follow : Cout = Cin ( e(KL.A/Q)-1 where KL= 1.7323.10-4 + 8.1060.10-4.1- 2.2717.10-5.1nCin - -2.0216.10<usp>-5, n-1.4067.10-8.A+1.1735.101.Q